2022
DOI: 10.3390/su14084475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Amendments on Soil Aggregate Stability, Carbon Sequestration, and Energy Use Efficiency in Wetland Paddy Cultivation

Abstract: A study was conducted to assess the effects of organic amendments on soil aggregates, carbon (C) sequestration, and energy use efficiency (EUE) during five consecutive Boro and Transplanted Aman rice seasons in Bangladesh during 2018–2020. Five treatments (viz., control (only inorganic fertilizers), cow dung (CD), vermicompost (VC), rice straw (RS), and poultry manure (PM)) were used. The organic materials were applied at 2 t C ha−1 season−1 to all the plots, except in the control treatment. Inorganic fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Excessive use of inorganic fertilizer alone causes an increased yield for some extent but this increased yield will not sustain for a long as continuous application of mineral fertilizers deteriorate soil health and create environmental pollution [3]. In terms of soil fertility and productivity, organic manures are superior to inorganic fertilizers because they improve soil health by improving physical, biological and chemical properties of soil [4][5][6][7][8] which result in higher yield and better-quality crop [9]. Moreover, application of organic amendments not only enhance the crop production but also can ameliorate soil salinity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive use of inorganic fertilizer alone causes an increased yield for some extent but this increased yield will not sustain for a long as continuous application of mineral fertilizers deteriorate soil health and create environmental pollution [3]. In terms of soil fertility and productivity, organic manures are superior to inorganic fertilizers because they improve soil health by improving physical, biological and chemical properties of soil [4][5][6][7][8] which result in higher yield and better-quality crop [9]. Moreover, application of organic amendments not only enhance the crop production but also can ameliorate soil salinity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that less power puddling can enhance the positive effects from returned straw, and it may relate to the improved nutrient supply capacity of soil. Previous research also indicated that when the soil's fertility was supplemented and enhanced, rice nutrient uptake and accumulation was notably improved [44][45][46], especially from heading stage to maturity stage, and less power puddling improved nutrient supply and retention capabilities by protecting soil structure [36,47]. Nutrients were released gradually as rice grew, ensuring a continuous nutrient supply for rice to uptake [48][49][50].…”
Section: The Effect Of Integrated Straw Return With Less Power Puddli...mentioning
confidence: 98%
“…Consequently, soil ammonium nitrogen content was lower when transplanting rice. However, after jointing stage, the protected soil aeration conditions facilitated the decomposition of straw [36,37], leading to a significant increase in soil ammonium nitrogen content from jointing to maturity stages. It can be inferred that less power puddling played a role in adjusting the timing of nutrient release.…”
Section: The Effect Of Integrated Straw Return With Less Power Puddli...mentioning
confidence: 99%
“…The addition of biofertilizers increases the speed of the decomposition of organic matter by a microorganism, and improve soil quality and plant productivity. Organic amendments appear positively to increase the C content and C uptake in the soil [16]. The application of biofertilizers integrated with chemical fertilizers in a sustainable manner can meet the nutritional needs of plants in addition to maintaining soil health and environmental safety [17].…”
Section: 1morphological Characterizationmentioning
confidence: 99%